Cyclin-Dependent Kinase 9 (CDK9) Inhibitor Atuveciclib Suppresses Intervertebral Disk Degeneration via the Inhibition of the NF-κB Signaling Pathway - Ni, Weiyu; Zhang, Feizhou; Zheng, Lin; Wang, Lili; Liang, Yi; Ding, Yuhong; Yik, Jasper H. N.; Haudenschild, Dominik R.; Fan, Shunwu; Hu, Ziang (Frontiers in Cell and Developmental Biology, 2020)
Intervertebral disk degeneration (IVDD) is a spinal disk condition caused by an inflammatory response induced by various proinflammatory cytokines, such as interleukin (IL)-1β and tumor necrosis factor (TNF)-α. cyclin-dependent kinase 9 (CDK9) is a transcriptional regulator and potential therapeutic target for many diseases, especially in regulating the activation of primary inflammatory response genes. Our study investigated a highly selective CDK9 inhibitor, atuveciclib, which protects nucleus pulposus (NP) cells from proinflammatory stimuli-induced catabolism. The effects of CDK9 inhibition were determined in human and rat NP cells treated with IL-1β in the presence or absence of atuveciclib or small interfering RNA target CDK9. Inhibition of CDK9 led to the attenuation of inflammatory response. In addition, rat intervertebral disk (IVD) explants were used to determine the role of CDK9 inhibition in extracellular matrix degradation. The rat IVDD model also proved that CDK9 inhibition attenuated IVDD, as validated using magnetic resonance imaging and immunohistochemistry. Taken together, CDK9 is a potential therapeutic target to prevent IVDD.